Effect of bile duct clamping versus no clamping on surgical site infections in patients undergoing pancreaticoduodenectomy: a randomized controlled study. Issue 7 (7th May 2020) - Singh, Harjeet; Krishnamurthy, Gautham; Kumar, Hemanth; Gorsi, Ujjwal; Kumar‐M, Praveen; Mandavdhare, Harshal; Sharma, Vishal; Yadav, Thakur D.
Abstract: Background: Infectious complications cause significant morbidity after pancreatoduodenectomy (PD). The impact of uncontrolled spillage of bile during PD has not been systematically studied. Methods: Patients undergoing PD for malignant lesions between March 2017 and May 2019 were considered for inclusion. All patients underwent standard pre‐operative preparation and antibiotic prophylaxis. After confirmation of resectability, the patients were randomized into one of the two groups: common hepatic duct clamping using atraumatic bulldog clamp after biliary division (Group I) or no clamping (Group II). Post‐operative outcomes including surgical site infection (SSI) were compared. Results: Fifty‐two patients were assessed for eligibility and eventually 40 were randomized (median age: 53.5 years, 28 (70%) males). Twenty patients were randomized into each group and 14 in each group had undergone pre‐operative biliary drainage. Incidence of co‐morbidities, operative time and blood loss were comparable between the two groups. SSI was significantly lower in Group I (4 (20%) versus 11 (55%), P = 0.02). Number needed to treat to prevent one SSI was 3. Incidence of intra‐abdominal collections was higher in Group II, though, not statistically significant (2 (10%) versus 6 (30%), P = 0.23). The duration of post‐operative antibiotics was significantly higher in Group II (7 IQR 4 versus 11 IQR 7 days, P = 0.04). Among the risk factor evaluated in the entire population, higher incidence of SSI was seen in patients with positive bile culture (13 (65%) versus 2 (10%), P = 0.04). Conclusion: Bile duct clamping during PD reduces risk of superficial SSI. Abstract : We performed a randomized comparison of clamping versus no clamping of bile duct in patients undergoing pancreaticoduodenectomy for malignant lesions were considered for inclusion. Post‐operative outcomes including surgical site infection were significantly lower in clamping group (4 (20%) versus 11 (55%), P = 0.02).